Pengaruh Store Atmosphere terhadap Kepuasan Konsumen di Mal Plaza Asia Tasikmalaya - Dwi Ajeng Rahayu; Iis Miati; Teguh Heri Widodo (Jurnal EMT KITA, 2026)
Current consumer behavior shows that shopping activities are no longer solely focused on fulfilling needs, but are also related to the experiences consumers gain while being in a particular place. This condition requires shopping center managers to create an atmosphere that supports visitors’ comfort and attractiveness. This study aims to examine the influence of store atmosphere on consumer satisfaction at Mal Plaza Asia Tasikmalaya and to identify the most dominant dimensions. This study employed a quantitative approach through a survey distributed to 100 respondents selected using incidental sampling. Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression analysis. The results showed that store atmosphere had a positive and significant influence on consumer satisfaction, with a contribution of 81.8% to the variation in consumer satisfaction. The external and general interior dimensions contributed more dominantly than the other dimensions in shaping consumer satisfaction. These findings confirm that store atmosphere plays a strong role in increasing consumer satisfaction, so atmosphere and environmental conditions should become major considerations in shopping center management strategies.